Autolysis of Pacific white shrimp (Litopenaeus vannamei) processing by-products: Enzymatic activities, lipid and protein oxidation, and antioxidant activity of hydrolysates. (February 2021) - Nikoo, Mehdi; Xu, Xueming; Regenstein, Joe M.; Noori, Farzaneh
Abstract: Autolysis (at fixed temperatures (FT) or gradually increasing temperatures (GIT) with different times) was studied by measuring enzymatic activities, lipid and protein oxidation, and antioxidant activity of Pacific white shrimp by-product hydrolysates. Trypsin had its highest activity at 40 °C, 2 h and pH 8 (45 mU/mL) followed by 40 °C, 3 h and pH 8 (40 mU/mL) (P ≤ 0.05). The increase in autolysis time and temperature was accompanied by a drop-in enzyme activity and TCA-soluble peptide content (P ≤ 0.05). The peptide fraction with MW < 1000 Da was the main peptide fraction, accounting for 97.0, 98.4, and 96.7% of total peptides in FT-40 (1 h), FT-60 (3 h) and GIT (3 h), respectively. The order of lipid oxidation was FT-60 > GIT > FT-50 > FT-40. FT-50 and FT-60 had the lowest sulfhydryl group content with a coincidental higher protein carbonyl (P ≤ 0.05). The higher temperatures of FT led to a decrease of essential amino acids, especially when autolysis time increased. GIT showed the highest DPPH radical scavenging activity, ferric reducing antioxidant power (FRAP) and metal chelating ability (P ≤ 0.05). Results might be useful to increase the value of Pacific white shrimp by-products for protein hydrolysates production using autolytic hydrolysis technology. Highlights: Autolysis for 2 h at 40 °C and pH 8.0 showed the highest trypsin activity. Highest lipid oxidation was observed at 60 °C, especially with increasing time. A gradual increasing temperature of 3 h showed the highest antioxidant activity. Both hydrolysated produced at fixed and gradual increasing temperatures were rich in small peptides.